The woman upstairs : a novel - Messud, Claire, 1966- (Alfred A. Knopf, 2013)
Relegated to the status of schoolteacher and friendly neighbor after abandoning her dreams of becoming an artist, Nora advocates on behalf of a charismatic Lebanese student and is drawn into the child's family until his artist mother's careless ambition leads to a shattering betrayal.